Intracranial Large Artery Abnormalities and Association With Cerebral Small Vessel Disease in CADASIL - Zhang, Chen; Li, Wei; Li, ShaoWu; Niu, SongTao; Wang, XinGao; Yu, Xueying; Zhang, ZaiQiang (Frontiers in Neurology, 2020)
Background and objective: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited systemic arteriopathy, the classic feature of which is small vessel lesions. Studies on intracranial large arteries in CADASIL are not common. We aim to evaluate intracranial large arteries, describing the characteristics of large arteries in CADASIL and their association with cerebral small vessel associated lesions. Methods: Consecutive CADASIL patients from a single-center prospective cohort were analyzed. Brain magnetic resonance imaging and magnetic resonance angiography were performed to assess the intracranial large arteries and cerebral small vessels associated lesions' neuroimaging. Results: The study included 37 CADASIL patients. Of the patients, 28 of them (75.7%) had intracranial large artery abnormalities. Eighteen (48.6%) had congenital variations such as fenestration, vertebral artery (VA) hypoplasia and agenesis, or common trunk and fetus posterior cerebral artery. Seventeen (45.9%) had acquired anomalies such as arterial stenosis, prolongation, or tortuosity (seven of them had both congenital and acquired anomalies). CADASIL patients with anterior circulation middle cerebral artery (MCA) or internal cerebral artery (ICA) severe stenosis were more likely to have ipsilateral asymmetric white matter hyper-density (WMH) distribution. Patients with posterior circulation VA hypoplasia had a higher prevalence of posterior subcortical zone dominant WMH distribution. Conclusion: CADASIL patients can demonstrate various intracranial large artery abnormalities which might influence the development of microangiopathy. Assessment of great vessels seems essential in CADASIL.